Analysis of Medical Record Evaluation Based on KARS Standards at RS TK II Moh. Ridwan Meuraksa Jakarta - Wibowo, Markus; Yochanan, Elisha; Wahyudin, Ferdic Sukma (International Journal of Health Sciences, 2024)
This study focuses on evaluating the medical records at RS TK II Moh. Ridwan Meuraksa, Jakarta, in line with the standards set by the Komite Akreditasi Rumah Sakit (KARS). The evaluation aims to measure the quality of the hospital's medical record system, a critical aspect of hospital operations that impacts patient care and administrative efficiency. The research employs both qualitative and quantitative methods to assess the medical records against KARS standards. Key findings indicate that while the hospital meets basic compliance requirements, there are significant areas for improvement, particularly in the completeness and accuracy of records. Recommendations include the implementation of enhanced training programs for staff, regular audits, and the adoption of advanced electronic medical record systems. The study highlights the importance of adhering to established standards to ensure high-quality healthcare delivery and suggests that continuous improvement in medical record management is essential for achieving accreditation and improving overall patient outcomes.